Zur Darstellung der Tempora in ausgewählten Grammatiken des Deutschen - Kątny, Andrzej (Studia Germanica Posnaniensia, 2018)
The meaning of past tenses is presented in various grammars in different ways. It was especially the hypothesis of the aspect-oriented meaning of Perfekt tense that has been paid attention to; its supporters claim that German Perfekt and Plusquamperfekt tenses express the meaning of completed action. The analysis of works of scholars has proved that the basic meaning of Perfekt tense is expressing the concept of anteriority. In the following part a few grammars have been presented. Their authors analysed the meaning of Perfekt tense having discussed telic and atelic verbs.